Norway : Financial Sector Assessment Program-Technical Note-Systemic Liquidity. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
Norwegian banks and other financial institutions rely heavily on capital markets for liquidity and risk management. Liquidity conditions in the Norwegian financial sector are affected by central bank operations and the lending and funding activities of financial institutions, both domestically and abroad. Nearly 40 percent of the funding of Norwegian banks is obtained from market sources, using commercial paper, covered bonds, and senior unsecured bonds issued both domestically and abroad. Correspondingly, money markets, foreign exchange (FX) swap markets and bond markets are crucial to the credit intermediation process and a dislocation in these markets-the inability of financial institutions to roll over, or obtain new, funding-could have significant consequences for financial stability. Against this background, this note analyzes core funding markets for Norwegian banks and assesses Norges Bank's capacity to manage systemic liquidity conditions and counteract liquidity shocks in normal times and in times of stress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet